Can preoperative thyroglobulin antibody levels be used as a marker for well differentiated thyroid cancer?. Issue 1 (December 2016) - Hosseini, S.; Payne, R.; Zawawi, F.; Mlynarek, A.; Hier, M.; Tamilia, M.; Forest, V.
Abstract Background It has been reported that thyroglobulin antibody are more frequently elevated in patients with thyroid cancercompared to general population. This study aims at evaluating whether preoperative thyroglobulin antibody (TgAb) levels increase the likelihood that a thyroid nodule is malignant. Methods A retrospective review of 586 patients who underwent thyroidectomy was conducted. Demographic data, TgAb levels, and final histopathology were recorded. Patients were divided into two groups: TgAb positive (defined as TgAb ≥ 30 IU/ml) and TgAb low/negative (defined as TgAb < 30). Results Preoperative TgAb levels were available in 405 patients. There were 353 (87 %) patients in the TgAblow/negative group (malignancy rate: 50.42 %) and 52 (13 %) patients in the TgAb positive group (malignancy rate: 65.38 %). The sensitivity, specificity, positive predictive value and negative predictive value of TgAb ≥ 30 IU/ml for thyroid malignancy were 16.04 %, 90.67 %, 65.38 % and 49.58 %, respectively. The relative risk of having a malignant thyroid nodule when the TgAb titers were≥30 IU/ml was 1.30 (CI1.04-1.62) and the odds ratio was 1.86 (CI 1.01-3.41). Both the Pearson chi-square test (p = 0.024) and Fisher's exact test (p = 0.017) yielded statistical significance between the two groups. Conclusions In this study, patients with preoperative TgAb ≥ 30 IU/ml had a higher rate of malignancy when compared topatients with TgAb < 30 IU/ml. This suggests that an elevated TgAb level may indicate that a thyroid nodule is at an increased risk for malignancy.